A Two‐Stage Annealing Strategy for Crystallization Control of CH3NH3PbI3 Films toward Highly Reproducible Perovskite Solar Cells. Issue 26 (28th May 2018) - Zhang, Jing; Liang, Wensheng; Yu, Wei; Yu, Shuwen; Wu, Yiliang; Guo, Xin; Liu, Shengzhong (Frank); Li, Can
Abstract: The solvent‐engineering method is widely used to fabricate top‐performing perovskite solar cells, which, however, usually exhibit inferior reproducibility. Herein, a two‐stage annealing (TSA) strategy is demonstrated for processing of perovskite films, namely, annealing the intermediate phase at 60 °C for the first stage then at 100 °C for the second stage. Compared to conventional direct annealing temperature (DHA) at 100 °C, using this strategy, MAPbI3 films become more controllable, leading to superior film uniformity and device reproducibility with the champion device efficiency reaching 19.8%. More specifically, the coefficient of variation of efficiency for 49 cells is reduced to 5.9%, compared to 9.8% for that using DHA. The TSA process is carefully studied using Fourier transform infrared spectroscopy, X‐ray diffraction, and UV–vis absorption spectroscopy. It is found that in comparison with DHA the formation of hydrogen bonding and crystallization of perovskite are much slower and can be better controlled when using TSA. The improvements in film uniformity and device reproducibility are attributed to: 1) controllable MAPbI3 crystal growth stemming from the progressive formation of hydrogen bonding between methylammonium and halide; 2) suppression of intermediate phase film dewetting, which is believed to be due to its decreased mobility at the initial low‐temperature annealing stage. Abstract : A two‐stage annealing strategy is used to prepare perovskite solar cells achieving a power conversion efficiency of 19.8% with high reproducibility. Comparing to the conventional high temperature annealing, the first annealing stage at lower temperature can slow down the crystallization process and make it better controlled. Furthermore, the strategy retards the dewetting of the intermediate phase and obtains MAPbI3 film with high quality.